Southeast Asia in the New World Order
XX, 320 p.
Keywords: This multi-authored book looks at one of the most dynamic regions of the Third World within the context of the rapidly changing international system of the 1990s. Among the many themes it explores are ASEAN's new political roles and new modes of economic cooperation, the growing importance of ecological and human rights issues, the policies of the major external powers towards the region, the Cambodian and Spratly conflicts, and the relevance of Southeast Asian experience in the 'New World Order' to the ongoing theoretical debates about democracy, the market, the state and multilateralism.